PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL (STUDI DI JEMBRANA BALI) - Saihu Saihu (Sekolah Tinggi Agama Islam Al Hidayah, 2019)
This paper discusses the ethnopedagogy-based education model in Jembrana. The paper focuses on exploring the impact of ethnopedagogy-based education on the process of interaction and integration that leads to peaceful practices in Hindu and Muslim communities in Jembrana. Data sources are obtained through unstructured observation and interviews during 2017 to 2018. The writing uses the mosaic analogy theory proposed by Issac Baer Bekson (1891-1975) and peace education proposed by John Dewey (1859-1952). Writing shows that through an ethnopedagogy-based education process can shape the character of Hindus and Muslims in Jembrana to be humanistic, tolerant and inclusive. This paper also shows that to shape the character and character of Hindus and Muslims in Jembrana as well as to foster diversity understanding, is through a male tradition, thus the interaction of Hindu and Muslim communities in Jembrana leads to the process of association, integration, complementation and sublimation.